Spatial congruence between carbon and biodiversity across forest landscapes of northern Borneo - Labrière, N.; Locatelli, Bruno; Vieilledent, G.; Kharisma, S.; Basuki, I.; Gond, Valéry; Laumonier, Y. (Elsevier, 2016)
Understanding how carbon and biodiversity vary across tropical forest landscapes is essential to achieving effective conservation of their respective hotspots in a global context of high deforestation. Whether conservation strategies aimed at protecting carbon hotspots can provide co-benefits for biodiversity protection, and vice versa, highly depends on the extent to which carbon and biodiversity co-occur at the landscape level. We used field measurements and easily accessible explanatory variables to model aboveground carbon density, soil carbon density and tree alpha diversity (response variables) over a mostly forested area of northern Borneo. We assessed the spatial relationships between response variables and the spatial congruence of their hotspots. We found a significant positive relationship between aboveground carbon density and tree alpha diversity, and an above-than-expected-by-chance spatial congruence of their hotspots. Consequently, the protection of areas of high aboveground carbon density through financial mechanisms such as REDD+ is expected to benefit tree diversity conservation in the study area. On the other hand, relationships between soil carbon density and both aboveground carbon density and tree alpha diversity were negative and spatial congruences null. Hotspots of soil carbon density, mostly located in peatlands, therefore need specific conservation regulations, which the current moratorium on peat conversion in Indonesia is a first step toward.